Možnosti využití adaptačního modelu Calisty Royové v současném ošetřovatelství - Kaas, Jiří; Tóthová, Valérie (Ošetrovateľstvo, 2015)
Aim: The study goal consists in mapping the opportunities of use of Calista Roy adaptation model in current nursing. Methods: The submitted article was processed by survey study method. Contents analysis of studies published within scientific databases was used for data collection. The search took place through key words under use of Boolean operators „AND“ and „OR“. The following key words were chosen: adaptation; nursing; Calista Roy; Roy adaptation model. Results: Based on the analysis of the published works, it was found out that the Roy adaptation model is a broadly applicable model in the conditions of current nursing. The most published studies were focused on the model application within internal nursing. But other clinical fields, nursing research or education of non-medical health care professionals were not omitted either. Conclusion: It can be stated in summary that Calista Roy adaptation model is a flexible and broadly applicable framework that can be effectively used both for ill and for healthy individuals.
Keywords: dospělí; adaptace psychologická; Nurse Clinicians; Adult; dítě; senioři; lidé; Child; ošetřovatelské modely; Adaptation, Psychological; Models, Nursing; Aged; Female; zdravotní sestry v klinické praxi; Humans; mužské pohlaví; Male; ženské pohlaví